Profil santé mentale des communautés francophones en situation minoritaire au Canada. Rapport abrégé - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa; Colman, Ian (Université d'Ottawa et Institut du Savoir Montfort, 2019)

Ma santé, ta santé, notre santé. Étude sur la santé mentale et les comportements à risque des jeunes adultes dans cinq universités au coeur du Canada - de Moissac, Danielle; Gueye, Ndeye Rokhaya; Rocque, Rhéa (Consortium national de formation en santé, Université de Saint-Boniface, 2019)
La transition de l’adolescence à la vie adulte constitue une des plus importantes transitions de la vie. À ce stade, le jeune doit développer des habiletés pour être en mesure de se prendre en charge et gérer ses responsabilités académiques et financières tout en maintenant un mode de vie sain. Des études démontrent que des perturbations à ce stade de vie peuvent avoir des conséquences importantes sur la santé psychologique et l’adaptation au changement, et qu’une instabilité émotionnelle peut avoir des retombées sur la performance et le fonctionnement psychosocial. Le milieu universitaire occupe une place privilégiée en tant que lieu d’intervention pour la promotion de la santé pour ces jeunes en raison du contact direct avec les étudiants au cours de plusieurs années. Une stratégie en matière de santé mentale, développée par la Commission de la santé mentale du Canada, souligne que les efforts de promotion en santé mentale et de prévention des troubles mentaux seront plus efficaces si les axes suivants sont respectés 1) savoir à qui s’adresser; 2) renforcer les éléments de protection et réduire les facteurs de risque; 3) fixer des buts clairs; 4) donner aux collectivités ce dont elles ont besoin pour agir; et 5) planifier pour le long terme. Ce projet de recherche s’inspire de cette stratégie : notre but à long terme est de favoriser le bien-être des jeunes adultes qui fréquentent un établissement universitaire en développant un outil de dépistage et des initiatives d’appui soutenables sur le campus et dans la communauté, selon les ressources disponibles. Pour ce faire, nous devons d’abord prendre connaissance de l’état de santé mentale de la population étudiante et des facteurs de risques et de protection qui leur sont propres. Ainsi, les efforts de prévention seront plus efficaces puisqu’ils seront conçus en fonction des besoins de la population cible et en consultation avec cette dernière. Cette étude a été menée dans cinq universités dans trois provinces, soit le Manitoba, l’Ontario et le Québec, dans le but de mieux comprendre l’effet du contexte linguistique sur la santé mentale et les comportements à risque des jeunes universitaires. Les cinq établissements choisis sont principalement des petites universités en contexte linguistique majoritaire (Brandon University et Université du Québec en Abitibi-Témiscamingue) ou minoritaire (Université de Saint-Boniface et Université Bishop’s). De plus, des participants de l’unique université bilingue du pays (Université d’Ottawa) ont participé. Ainsi, nous serons en mesure d’analyser les données en fonction de divers facteurs déterminants, dont le milieu linguistique dans lequel évolue l’étudiant. L’objectif principal de l’étude est de prendre connaissance de l’état de santé mentale et des comportements à risque prédominants des jeunes universitaires en contextes linguistiques majoritaires et minoritaires au Canada et d’identifier les facteurs de protection et de risque associés à leur bien-être. Notre but ultime est d’appuyer les étudiants, particulièrement ceux dans le besoin, dans leur atteinte d’une réussite académique. Ce rapport est descriptif : il présente les données générales se rapportant aux profils sociodémographique et ethnolinguistique, à l’état de santé mentale et aux comportements associés à cet état, ainsi qu’à la sécurité routière, au taxage et au harcèlement sexuel, aux pratiques sexuelles, à la consommation d’alcool, de drogues et de tabac, et à l’usage des nouvelles technologies; le tout, selon le genre et pour chacun des établissements d’enseignement postsecondaire. Un sondage a été distribué, sur papier ou en ligne, en fin novembre 2018 et en février 2019; au total, 2075 étudiants ont participé. Des analyses statistiques de fréquences et de proportions, selon le genre, ont été utilisées pour décrire les participants et leurs comportements.
fs-ref-orig: de Moissac, D., Gueye, N. R. et Rocque, R. (2019). Ma santé, ta santé, notre santé. Étude sur la santé mentale et les comportements à risque des jeunes adultes dans cinq universités au coeur du Canada. Consortium national de formation en santé, Université de Saint-Boniface et Université du Québec en Abitibi-Témiscamingue. fs-code-orig: de Moissac-2019b

My Health, your health, our health. A study on mental health and risk-taking behaviors of young adults on five university campuses in the heart of Canada - de Moissac, Danielle; Gueye, Ndeye Rokhaya; Rocque, Rhéa (Consortium national de formation en santé, Université de Saint-Boniface, 2019)
The transition from adolescence to adulthood is a time of dramatic change in one’s life. At this stage, youth are developing skills to be able to support themselves and manage academic and financial responsibilities, while maintaining a healthy lifestyle. Studies have shown that disturbances at this stage may have a strong impact on one’s psychological health and ability to adapt to change; emotional instability may have repercussions on performance and psychosocial functioning. Due to direct contact with young adults, postsecondary institutions are priviledged settings for health promotion activities. A mental health strategy developed by the Mental Health Commission of Canada suggests that to successfully promote health, and treat and prevent mental health issues, the following should be considered: 1) know who to reach; 2) strengthen protective factors and reduce risk factors; 3) set clear goals; 4) give communities what they need to take action; and 5) plan for the long term. This research project builds on this strategy. Our long term goal is to promote the well-being of university students by developing a screening tool and developing sustainable initiatives on campus and within the community, taking into consideration available resources. As such, we must first gain insight into the mental health status of the student population, including the risk and protective factors specific to these students. Thus, health promotion efforts will be more efficient, as they will have been created according to student needs and in consultation with this population. This study was conducted in five universities in three provinces, Manitoba, Ontario and Quebec, to gain insight into the impact of the linguistic context on mental health and risk-taking behaviors of students. The five participating universities were chosen mainly because of their small size and linguistic environment: Brandon University and the Université du Québec en Abitibi-Témiscamingue are in linguistic majority settings, whereas the Université de Saint-Boniface and Bishop’s University are in linguistic minority communities. In addition, participants were recruited from the only bilingual university in the country (University of Ottawa). Thus, data will be analysed according to various influencing factors, including the linguistic environment. The main objective of this study is to gain insight into the mental health status and predominant risk behaviors of university students in both majority and minority linguistic settings in Canada and to identify protective and risk factors relative to their well-being. The ultimate goal is to help those in need achieve academic success. This report is descriptive: it presents general data related to sociodemographic and ethnolinguistic profiles, mental health and related behaviors, road safety, bullying and sexual harassment, sexual practices, alcohol, drug and tobacco use and use of new technologies, according to gender, for each of the postsecondary institutions. A survey was conducted online or in print form at the end of November 2018 and in February 2019. In total, 2075 students participated. Statistical analysis of frequencies and proportions according to gender were used to describe participants and their behaviors
fs-ref-orig: de Moissac, D., Gueye, N. R., & Rocque, R. (2019). My Health, your health, our health. A study on mental health and risk-taking behaviors of young adults on five university campuses in the heart of Canada. Consortium national de formation en santé, Université de Saint-Boniface et Université du Québec en Abitibi-Témiscamingue. fs-code-orig: de Moissac-2019c

Substance use and impaired driving prevalence among Francophone and Anglophone postsecondary students in Western Canada - Gueye, Ndeye Rokhaya; Bohémier, Monique; de Moissac, Danielle (Addictive Behaviors Reports, 2019)
Introduction Substance use and impaired driving increase risk of motor vehicle crashes and deaths. Individual, socio-economic and -cultural factors are associated with these at-risk behaviors; however, little is known if differences exist between the Anglophone majority and minority Francophone populations in Canada. This article describes prevalence of substance use, impaired driving and driving practices by postsecondary student and compares Francophones and Anglophones with respect to these behaviors. Methods Postsecondary students between 18 and 24 years attending a Francophone university in Western Canada completed a paper-based survey during class-time. Results Prevalence of alcohol consumption, binge drinking and marijuana use in the past month were 88.6%, 64.2% and 22.7% respectively. Francophone participants were more likely to consume more alcohol, participate in drinking games, and consume marijuana during the past month than Anglophones. They were also more likely to report impaired-driving, speeding, distracted driving and being passenger in a motor vehicle driven by an impaired driver. Conclusion Awareness campaigns on campus highlighting the risks of substance use and unsafe driving practices should be strengthened and target Francophone students in linguistic minority communities.

The Forgotten: The Challenges Faced by Francophone Nursing Candidates following the Introduction of the NCLEX-RN in Canada - Lalonde, Michelle (Nursing Leadership, 2019)
In 2015, the traditional paper-and-pencil entry-to-practice exam in Canada was replaced by a computer-adaptive testing exam, the American National Council Licensure Examination for Registered Nurses (NCLEX-RN). As there are two official languages in Canada - English and French - the NCLEX-RN was translated to French. Although initially the pass rates for anglophone writers with the NCLEX-RN were lower than with the previous Canadian licensing exam, their pass rates have now increased. By contrast, francophone writers have continued to have lower pass rates, and a decreasing number of candidates are choosing to write the exam in French. A lack of access to French language preparatory resources is being reported by francophone graduates as one of the contributing factors. Canadian nursing regulators report that they are not responsible for ensuring that candidates have access to preparatory materials. However, given the bilingual culture and heritage in Canada, there is a responsibility to ensure equitable access to preparatory resources to ensure success on the licensing exam. This paper raises alarm about the decreasing number of francophone graduates writing the NCLEX-RN in French and the ongoing delivery of safe, quality nursing care to francophone patients by nurses proficient in the French language.

Pratique # 8 : Une infirmière coordonnatrice bilingue en milieu hospitalier à Halifax (IWK Health) (Nouvelle-Écosse) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2019, mise à jour 2025). Pratique # 8 : Une infirmière coordonnatrice bilingue en milieu hospitalier à Halifax (IWK Health) (Nouvelle-Écosse). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: Savard-2025f

My health, your health, our health at uOttawa [infographic] - Université d'Ottawa; Consortium National de formation en Santé; Unversité de Saint-Boniface (2019)
fs-ref-orig: University of Ottawa, Consortium National de formation en Santé et Unversité de Saint-Boniface. (2019). My health, your health, our health at uOttawa [infographic]. fs-code-orig: University of Ottawa-2019

Ma santé, ta santé, notre santé à l'Université de Saint-Boniface [infographie] - Université de Saint-Boniface; Consortium National de formation en Santé (2019)
fs-ref-orig: Université de Saint-Boniface et Consortium National de formation en Santé. (2019). Ma santé, ta santé, notre santé à l'Université de Saint-Boniface [infographie]. fs-code-orig: Université de Saint-Boniface-2019